WILLIAMSON MODEL: AN APPLICATION OF INSTITUTIONAL TRANSFORMATION IN THE INDONESIAN DGT - Wihana Kirana Jaya; Anggi Rahajeng; Indra Bastian (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
A reform of tax administration in Indonesia has been carried out in several stages from 1983 to 2009. However, the changes are limited to the tax system of the DGT, it being the tax governing body in Indonesia, which has still has not managed to meet the tax revenue target (reflected through a tax ratio). A lack of authority caused the DGT (DGT) to face some difficulties in reaching the target and demonstrating the expected performance. The goal of this paper is to stress the needs of institutional transformation in DGT. By using the Williamson Model, this study focuses on evaluating the DGT institutionally and creating an alternative institutional transformation of the DGT. The international and domestic results of ascertaining best practices conclude that the DGT needs to change gradually, not with a ‘big bang’, and by providing the more flexible authority by remaining in the structure of Traditional Department or Single Directorate in the Ministry of Finance (SDMOF) which would lead to an organization structure which is semi-autonomous or a Unified Semi-autonomous Body (USB) that covers all the systems of taxation such as service, assurance, law enforcement and supporting roles.